Pengaruh Ekstrak Bunga Kecombrang (Etlingera elatior (Jack)) Terhadap Gambaran Histopatologi Lambung Pada Tikus Putih Jantan (Rattus norvegicus) Yang Diindukasi Streptozotocin - Palipadang, Matra Novalia; Alaydrus , Syafika; Tandi , Joni; Islamiati , Utami; Toding, Ficanata Adhiguna; Managanta , Vianda (Journal of Pharmaceutical and Sciences, 2026)
Background: Hyperglycemia induced by streptozotocin (STZ) increases oxidative stress and inflammatory responses that may lead to gastric mucosal damage. Kecombrang flower (Etlingera elatior (Jack)) contains flavonoids and other secondary metabolites with antioxidant, anti-inflammatory, and antihyperglycemic properties that are potentially gastroprotective. Objective: This study aimed to evaluate the effect of ethanol extract of kecombrang flower on the histopathological profile of the stomach in male white rats (Rattus norvegicus) induced by streptozotocin and to determine the most effective dose. Methods: This experimental in vivo study employed a posttest-only control group design. Twenty-five male rats were divided into five groups (n=5): normal control, negative control (STZ-induced), positive control (STZ + glibenclamide), extract 50 mg/kg body weight (BW), and extract 100 mg/kg BW. Streptozotocin was administered intraperitoneally at 40 mg/kg BW. Gastric tissues were examined histopathologically using hematoxylin-eosin staining and assessed based on degeneration, necrosis, and inflammation scoring. Data were analyzed using Kruskal–Wallis followed by Mann–Whitney test with Bonferroni correction (p<0.05). Results: Phytochemical screening confirmed the presence of alkaloids, flavonoids, saponins, and tannins in the extract. Statistical analysis showed significant differences among groups in degeneration (p=0.013) and inflammation (p=0.047), but not in necrosis (p=1.000). The 100 mg/kg BW dose demonstrated the most prominent protective effect, with lower degeneration and inflammation scores and an average gastric damage score of 1, comparable to the positive control group. Conclusion: Ethanol extract of kecombrang flower at a dose of 100 mg/kg BW effectively reduced gastric histopathological damage in streptozotocin-induced male rats, indicating its potential gastroprotective activity through antioxidant and anti-inflammatory mechanisms.